KOMPARASI INDEKS KEANEKARAGAMAN DAN INDEKS DOMINANSI FITOPLANKTON DI SUNGAI CILIWUNG JAKARTA - Marlenny Sirait; Firsty Rahmatia; Pattulloh Pattulloh (Jurnal Harpodon Borneo, 2017)
Phytoplankton is a biological parameter that can be used as an indicator to evaluate the quality and level of fertility of a water. Changes in water quality as a result of the large load of nutrients entering the Ciliwung River will affect the life of phytoplankton. This study aims to see the comparative index of diversity (H ') and the Dominant Index (D) of phytoplankton in Ciliwung River from upstream to downstream. The study was conducted from December 2016 to February 2017 from upstream to downstream of the Ciliwung River. From the index analysis of diversity and index of dominance, there was a significant difference, where the downward index of diversity (H ') of phytoplankton was lower, ranged between 1,21 and 2,6 (the index of diversity ranging from low to medium).  Otherwise, the dominance index showed the opposite result. The more downstream the dominance index is higher than the upstream, ranged between 0,09 and 0,68. Thus the index of diversity and the index of phytoplankton dominance has a relationship inversely. Differences of diversity index and dominance index in upstream to downstream poses an imbalance of ecosystem in Ciliwung River.             Keywords: Ciliwung, diversity index, Dominant Index, Phytoplankton